Ability and an aptness GPR for coastal land description at Kuala Perlis / Muhammad Nurul Anuar Azman - Azman, Muhammad Nurul Anuar (2022)
Ground Penetrating Radar (GPR) has been used in a wide range of applications including soil layer thickness measurements and concrete inspections. To conduct a GPR investigation, an electromagnetic microwave is emitted into the matter under inquiry. Objects with differing dielectric characteristics than the medium being studied will reflect the waves and be picked up by the receivers built into the antenna. Malaysia is about 329,293 km square land. As a whole, the coast is about 4,809 km long. There is a lot of social and economic value in Malaysia's coastal area. Most of the people live in this area, and it is the centre of business. This research is to examine the ability and aptness of the GPR to extract the underground data at Kuala Perlis. The main objective is to explore the underground data at Kuala Perlis using GPR. The final output is the 2D image of the underground in the coastal area. The result of ground truth data is process by using Reflex W software and the coordinates was collected. The data after being processed will digitize and the sediment and underground materials was analysed. The diffraction hyperbola was used and the calculation for dielectric constant have been performed to make sure the types of earth materials known.